2005
DOI: 10.1016/j.femsle.2005.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary origins and sequence of theEscherichia coliO4 O-antigen gene cluster

Abstract: Escherichia coli express many types of O antigen, present in the outer membrane of the Gram-negative bacterial cell wall. O-Antigen biosynthesis genes are clustered together and differences seen in O-antigen types are due to genetic variation within this gene cluster. Sequencing of the E. coli O4 O-antigen gene cluster revealed a similar gene order and high levels of similarity to that of E. coli O26; indicating a common ancestor. These lateral transfer events observed within O-antigen gene clusters may occur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Studies mostly based on Salmonella enterica and E. coli (D’Souza et al, 2005; Hu et al, 2010; Reeves et al, 2013) have previously suggested that OAg biosynthetic operons in bacterial pathogens were acquired by horizontal genetic transfer from species with a low GC content. Moreover, horizontal exchange of O-specific antigen biosynthetic genes among phylogenetically distinct P. aeruginosa strains was observed and serotype switching was found to be the result of horizontal transfer and genetic recombination of LPS biosynthetic genes originating from an multidrug-resistant taxonomic outlier P. aeruginosa strain (Thrane et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Studies mostly based on Salmonella enterica and E. coli (D’Souza et al, 2005; Hu et al, 2010; Reeves et al, 2013) have previously suggested that OAg biosynthetic operons in bacterial pathogens were acquired by horizontal genetic transfer from species with a low GC content. Moreover, horizontal exchange of O-specific antigen biosynthetic genes among phylogenetically distinct P. aeruginosa strains was observed and serotype switching was found to be the result of horizontal transfer and genetic recombination of LPS biosynthetic genes originating from an multidrug-resistant taxonomic outlier P. aeruginosa strain (Thrane et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The G + C content within the O antigen clusters also greatly differs from gene to gene, indicating that the gene clusters might have been assembled from multiple horizontal transmission events and from several sources over a much longer time (Lerouge and Vanderleyden 2002). The role of lateral gene transfer in the evolution of O antigen clusters and O antigen diversification has been well described in Salmonella (Perepelov et al 2011;Reeves et al 2013), Escherichia (D'Souza, Samuel andReeves 2005;Hu et al 2010;Azmuda et al 2012), Vibrio (González-Fraga et al 2008Wildschutte et al 2010), Yersinia (Cunneen and Reeves 2007) and Brucella (Wattam et al 2014). Another mechanism of variation involves large chromosomal rearrangements.…”
Section: Lateral Gene Transfer Recombination and Genetic Rearrangementsmentioning
confidence: 97%
“…The O-antigen gene clusters for many O groups have now been sequenced (Marolda and Valvano, 1993; Bastin and Reeves, 1995; Amor and Whitfield, 1997; Wang and Reeves, 1998; Wang L et al , 1998, 2001, 2002, 2007, 2009, 2010, Paton and Paton, 1999; Shepherd et al , 2000; D'Souza et al , 2002, 2005; Grozdanov et al , 2002; Perelle, et al , 2002; Shao et al , 2003; Fratamico et al , 2003, 2005, 2009a, b, 2010; Feng et al , 2004a, b, 2005a, b, 2007; Guo et al , 2004, 2005; Beutin et al , 2005a, b, 2007; DebRoy et al , 2005; Cheng et al , 2006, 2007; Cunneen and Reeves, 2007; Han et al , 2007; Liu Y et al , 2007, 2008; Liu B et al , 2010; Ren et al , 2008; Perepelov et al , 2009, 2011a, b; Wang Q et al ., 2009, 2010a, b; Li et al , 2010a, b). DNA sequences for about 95 O-antigen gene clusters have been deposited in GenBank so far, and the accession numbers are listed in Table 1.…”
Section: O Antigen Detectionmentioning
confidence: 99%